2021
DOI: 10.1021/acs.energyfuels.1c03418
|View full text |Cite
|
Sign up to set email alerts
|

Proof-of-Concept Molten Lithium–Selenium Battery

Abstract: Most space missions utilize energy storage, such as a rechargeable battery onboard the spacecraft. Therefore, a continuing evolution of battery performance can benefit a wide gamut of space science missions conducted or planned by NASA and worldwide space agencies. Venus presents the most significant challenge to energy storage systems due to a combination of high temperature (465 °C) and the presence of corrosive gases (CO 2 , CO, SO 2 , and N 2 ). On a NASA-funded project, a high-temperature (465 °C) lithium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Recently some new concepts of molten lithium metal batteries have been created, which consists of liquid lithium anodes, alloy (Se Sn, Bi, and Pb) liquid cathodes and lithium ion conductors as solid electrolytes. For example, Ashish Gogia et al 118 reported a high-temperature lithium–selenium (Li‖Se) battery consisting of an anode of molten Li, a lithium-ion conducting ceramic electrolyte (garnet-type Li 6.4 Al 0.2 La 3 Zr 2 O 12 , LLZO), and a cathode of Se. the molten Li‖Se cell functional at 465 °C showed a stable open circuit voltage for 17 h and stable electrochemical cycling with different current rates.…”
Section: Interfaces Between Molten Electrodes and Solid Electrolytesmentioning
confidence: 99%
“…Recently some new concepts of molten lithium metal batteries have been created, which consists of liquid lithium anodes, alloy (Se Sn, Bi, and Pb) liquid cathodes and lithium ion conductors as solid electrolytes. For example, Ashish Gogia et al 118 reported a high-temperature lithium–selenium (Li‖Se) battery consisting of an anode of molten Li, a lithium-ion conducting ceramic electrolyte (garnet-type Li 6.4 Al 0.2 La 3 Zr 2 O 12 , LLZO), and a cathode of Se. the molten Li‖Se cell functional at 465 °C showed a stable open circuit voltage for 17 h and stable electrochemical cycling with different current rates.…”
Section: Interfaces Between Molten Electrodes and Solid Electrolytesmentioning
confidence: 99%
“…(L) Initial molten LSeBs electrochemical data showing open‐circuit voltage as a function of temperature 465°C at a rate of 10°C min −1 . Reproduced with permission 91 . Copyright 2021, American Chemical Society.…”
Section: Design and Modification Of The Asslsebsmentioning
confidence: 99%
“…Inspired by this, Jitendra Kumar group 91 constructed LSeBs comprising of a liquid Li anode, a Li 6.4 Al 0.2 La 3 Zr 2 O 12 (LLZO) SSE that conducts Li + , and a cathode of Se/C which molten Se mixed with carbon at 450°C (Figure 11K). The LLZO samples were prepared by using a traditional solid‐state method 92 .…”
Section: Design and Modification Of The Asslsebsmentioning
confidence: 99%
“…This battery has a high reversible capacity of 652 mA h g −1 (96% of theoretical capacity) and exhibits favorable capacity retention during cycling. Kumar et al also showcased the functionality of a high-temperature molten Li–Se battery cell with a garnet-type solid-state electrolyte (LLZO) operating at 465 °C ( Figure 4 b), which is essential for powering future space exploration missions [ 88 ]. The cells demonstrated a stable open-circuit voltage for 17 h and were subjected to electrochemical cycling at various current rates.…”
Section: Solid-state Lithium Battery With Conversion-type Cathodesmentioning
confidence: 99%
“…Reproduced with permission from ref. [ 88 ]. Copyright 2021, ACS Publications (Washington, DC, USA).…”
Section: Figurementioning
confidence: 99%